Epstein-Barr virus-associated lymphomas: biology, molecular genomics and precision oncology - Datta, Soumyadeep; Gogia, Ajay; Mallick, Saumyaranjan (Frontiers in Oncology, 2025)
Epstein-Barr virus (EBV) is a ubiquitous human gamma-herpesvirus causally linked to a diverse spectrum of lymphoid malignancies. This review provides a comprehensive overview of EBV-associated lymphomas, encompassing their global epidemiology, the intricate pathogenesis driven by viral latency proteins and complex host immune interactions, and the varied clinical presentations of distinct subtypes. We delve into the detailed pathological features, molecular characteristics, and diagnostic strategies for classic Hodgkin lymphoma (cHL), Burkitt lymphoma (BL), diffuse large B-cell lymphoma (DLBCL), post-transplant lymphoproliferative disorder (PTLD), and extra-nodal NK/T-cell lymphoma, nasal type (ENKTL). Current subtype-specific treatment paradigms are critically evaluated, along with a thorough exploration of emerging therapeutic avenues, including novel immunotherapeutic approaches such as immune checkpoint inhibitors, adoptive cell therapies like EBV-specific cytotoxic T lymphocytes and chimeric antigen receptor T-cells (CAR-T), and targeted molecular therapies. Finally, we highlight the persistent challenges, critical knowledge gaps, and promising future prospects, including preventative and therapeutic vaccine strategies, aimed at optimizing diagnostic precision and improving long-term outcomes for patients afflicted with these heterogeneous and often aggressive diseases.